In Vitro Antibacterial Spectrum of Sodium Selenite against Selected Human Pathogenic Bacterial Strains - Mohammad Firoz Alam; Mohammed M. Safhi; Sivakumar Sivagurunathan Moni; Aamena Jabeen (Scientifica)
The objective of this investigation was to predict the antibacterial properties of sodium selenite against selected human pathogens. A group of six human bacterial pathogens including Staphylococcus aureus, Streptococcus pyogenes, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella planticola were utilized for screening. The spectrum of activity was qualified based on zone of inhibition. Our study demonstrated that sodium selenite exhibits a strong spectrum of activity against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Klebsiella planticola. The spectrum of activity was compared with standard ciprofloxacin disc (5 μg/disc) and observed to have satisfactory effect.